REWARD SEBAGAI INSTRUMEN MANAJEMEN MUTU PENDIDIKAN - Nita Lustia; Sukarman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research analyzes the role of reward as an educational quality management instrument in improving teacher performance and student achievement at Madrasah Aliyah Negeri 1 Jepara. Employing a descriptive qualitative approach, the study was conducted through participatory observation, in-depth interviews with the madrasah principal, vice principal for student affairs, homeroom teachers, madrasah committee, teachers, and students, as well as documentation study of scholarships from 2023-2025. Data analysis using Miles and Huberman model encompasses data reduction, data display, and conclusion drawing with source and method triangulation to ensure data validity. Research findings indicate that the reward system at MAN 1 Jepara is consistently implemented with substantial fund allocation reaching 120-136 million rupiah annually for teachers and students. The system's excellence lies in comprehensive criteria integrating academic achievement, attitude, discipline, participation, and socio-economic conditions. The reward system is integrated with the Internal Quality Assurance System through PPEPP cycle involving all stakeholders in transparent and accountable processes. Positive impacts include increased teacher intrinsic motivation to innovate in teaching and professionalism, as well as enhanced student learning motivation, discipline, and active participation. The reward system contributes to madrasah quality culture formation through collective spirit, healthy competition, and shared commitment to achieving excellence standards. The research recommends developing structured assessment instruments, funding diversification, continuous character development, and integrated management information systems to optimize reward impact on educational quality.